Evaluate the efficacy of the Ayurveda treatment regime in the management of Kitibha kushta with special reference to psoriasis: Case series - Rajapaksha, R.A.J.W.; Jayawardhana, N.D.N.; Weerasekara, K.R. (University of Colombo, 2025)
Kitibha is classified as one among a Kshudra kushtha in Ayurveda texts and it can be correlated with psoriasis in modern medicine. Ayurveda literature describes numerous treatment modalities for this disease and specially indicates the Panchakarma therapies according to the involvement of predominant Dosha. Therefore, this study was conducted to evaluate the efficacy of Ayurveda treatment regime for Kitibha kushta with the involvement of Pitta dosha. After obtaining ethical clearance, a total of five patients diagnosed with Kitibha were selected from the Kayachikitsa ward of Minneriya Ayurveda Base Hospital and the Kayachikitsa and Panchakarma wards of the Ayurveda National Hospital, Borella, Sri Lanka. The treatment regime included initially Tripal guggul decoction with Manibadra churna, followed by the Grita pana in Vardhamana krama until the presence of Samyag snigdha lakshana. After the administration of Purva karma (applied Pinda thaila and Nadisveda with Dasamul kwatha), Virechana karma was done with Trivrut dantyadi decoction. Assessment was done using the Psoriasis Area and Severity Index (PASI) scores before and after the treatment. Patients were observed over a period of one month. The response to the treatment was recorded as percentage as per the following calculation: (Before treatment - after treatment)/before treatment) x 100. After the treatment regime, all patients showed symptomatic improvement, as evidenced by reductions in PASI scores, reflecting decreased skin involvement and reduced severity of erythema, induration, and desquamation. One patient showed a marked reduction of 77.8%, while two patients demonstrated moderate improvements of 58% and 55%. Two patients exhibited mild improvements of 33.3% and 18%. The results of this case series suggest that the Ayurveda intervention including Virechana karma shows promising efficacy in the management of Kitibha kushata (psoriasis) with predominant involvement of Pitta dosha. However, randomized controlled studies with larger sample sizes and longer follow-up durations are necessary to validate these findings and explore the underlying mechanisms from both Ayurvedic and biomedical perspectives.
Keywords: Kitibha; Psoriasis; Virechana karma; Trivrut danthyadi decoction